Caribi Mobile Application Based on Radio Frequency Identification (RFID) for Internet of Things (IoT) - Faridah, Linda; Rahayu, Andri Ulus; Shopa, Rahmi Nur; Sulastri, Heni; Hiron, Nurul; Nursuwars, Firmansyah M S (SOTVI, 2022)
Nowadays, the e-commerce industry in Indonesia is growing substantially and expanding annually. This is one of the revolutions that has affected various aspects of life, including animal husbandry. In Indonesia, buying and selling livestock has become routine; however, it is still conducted conventionally. Therefore, a system is required to facilitate online purchasing and selling transactions; thus, farmers can expand their enterprises. This study aimed to develop a mobile application for the online purchase and sale of livestock. The Caribi Mobile Application is built with a system that can provide consumers with accurate information by recording the tracks of each animal that will be sold. Each animal’s age, weight, and recent pictures are included. Tag RFID-based Internet of Things (IoT) system is used in searching for mobile applications. The RFID Tag System is used to carry out two functions at once, namely assistance and security. This application is designed to integrate livestock data from the internet and save it in a database. This study’s findings demonstrate that the system can read the data related to each farm animal. Additionally, the system has created data on the weights of each animal, which anyone with access to the Caribi Mobile Application can view.